Anthelmintic Activity of Extracts and Active Compounds From Diospyros anisandra on Ancylostoma caninum, Haemonchus placei and Cyathostomins - Flota-Burgos, Gabriela Janett; Rosado-Aguilar, José Alberto; Rodríguez-Vivas, Roger Iván; Borges-Argáez, Rocío; Martínez-Ortiz-de-Montellano, Cintli; Gamboa-Angulo, Marcela (Frontiers in Veterinary Science, 2020)
The present study aimed to evaluate the anthelmintic activity of leaf and bark extracts of Diospyros anisandra collected during different seasons and their major constituents on eggs of Ancylostoma caninum, Haemonchus placei and cyathostomins. Specifically, the eclosion inhibition of the methanolic extracts of the leaves and bark of D. anisandra collected during the dry and rainy seasons (600–37.5 µg/ml) were evaluated in addition to the fractions, sub-fractions (300–37.5 µg/ml) and active major constituents (150–2.3 µg/ml). The rainy season bark extract had the highest percentage of eclosion inhibition (PEI) against the evaluated nematodes (≥ 90% at 75 µg/ml) along with high ovicidal activity (90.0% to 93.4% at 75 µg/ml). The purification of the rainy season bark extract showed that its biological activity came from the non-polar n-hexane fraction (≥ 93% at 75 µg/ml). The bioguided fractionation pointed to sub-fraction 5 as having the highest anthelmintic activity against the three evaluated genera of nematodes (PEI ≥ 93% at 37.5 µg/ml). Gas chromatography and mass spectrometry revealed that the major constituent in sub-fraction 5 was plumbagin. Upon evaluation, plumbagin was confirmed to be responsible for the anthelmintic activity of D. anisandra, with a PEI ≥ 90% at 2.3 µg/ml on the three evaluated nematodes. Additionally, the compounds betulin and lupeol in the bark of D. anisandra were evaluated but presented low anthelmintic activity (PEI ≤ 5.3% at 2.3 µg/ml). In conclusion, the rainy season bark extract of D. anisandra exerts a high ovicidal activity against the eggs of the three studied nematodes. Plumbagin is the active compound responsible for this activity and represents a potential alternative for the control of different genera of gastrointestinal nematodes given the current scenario of anthelmintic resistance.